Development of imaging with MeV ions - Norarat, Rattanaporn (2013)
MeV ions have wavelengths much less than 1 nm, penetrate deeply into solid materials and interact strongly with atoms in the target by Coulomb forces. This makes them well suited for producing images on a μm or nm scale. In this thesis two complementary aspects of imaging with ion beams have been investigated, namely; the micropatterning by MeV ion beam lithography and obtaining microscopic images by MeV ion microscopy. An overview of the DREAM microbeam project is presented. A description of the DREAM facility, the ion optical design and the data collection system are given. Ions with energies in the MeV range can penetrate into materials along straight trajectories because of their high momentum and create the vertical sidewalls in resist materials after development with a suitable solvent. This makes MeV ion beam lithography a useful tool for direct-writing of high aspect ratio structures. This technique is receiving a growing interest for applications such as microfluidics, optical waveguide devices and bioscience applications. MeV ion microscopy can be used to study the structure of cells or sub-cellular organelles in biomedical imaging. The principle underlying this technique is that a finely focusedMeV ion beam is scanned over the biological sample. Mapping in 2D (in some cases even 3D) is performed by synchronous collection of Ion Beam Analysis (IBA) signals such as Scanning Transmission Ion Microscopy (STIM), Proton Induced Fluorescence (PIF), Rutherford Backscattering Spectrometry (RBS) and Particle Induced X-ray Emission (PIXE). In this thesis work we investigated how the MeV ion fluence influences the lithographic images in PMMA resist polymer. This study provided important ion exposure information for selecting the optimal conditions for MeV ion beam lithography. It was found that the width of the exposure window between complete clearing and the onset of cross-linking depended on the ion species. Protons because of they have the widest exposure window and also the longest range are best suited for lithography. The use of Proton Induced Fluorescence (PIF) imaging to image uv fluorescent markers in cells in conjunction with imaging of the cell structure using Direct-Scanning Transmission Ion Microscopy (Direct- STIM) was shown to give images with much better resolution than could be obtained with a conventional uv fluorescent optical microscope. This points the way to new uses of this method for tracing biomolecule pathways with higher resolution than is possible by optical microscopy. In addition, we have studied numerical image processing approaches to improve in an objective way the visual quality of the MeV ion microscope images which su↵er from speckle noise.